Керування мікроконтролерним пристроєм за допомогою web додатку - Оленич, П. С. (ХНУРЕ, 2023)
This work is devoted to finding the most convenient way to control a microcontroller device from the point of view of user experience. The common approaches to writing such software are considered and, based on their shortcomings, the use of a Web application as a control interface is proposed. Additionally, the prospects for launching such an application locally within the microcontroller are considered, which will allow connecting to such an interface from any device in the current network